2015
DOI: 10.2214/ajr.14.13663
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Performance of Whole-Body MRI as a Tool for Cancer Screening in Children With Genetic Cancer-Predisposing Conditions

Abstract: Unenhanced whole-body MRI is safe and produces excellent images. The high sensitivity, specificity, and NPV make whole-body MRI a valuable cancer screening tool in children with a genetic predisposition for cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
84
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 88 publications
(86 citation statements)
references
References 14 publications
1
84
0
1
Order By: Relevance
“…Considerable site-to-site variations arise from differing scanner platforms and technological capabilities, the tumors and syndromes under surveillance, and departmental/radiologist preference. The most recent published protocols specific for WBMRI in pediatric oncology utilize a fluid-sensitive sequence in the coronal plane, with additional optional sequences and imaging planes (1,(6)(7)(8)(17)(18)(19), and are summarized in Table 2. As documented in the table, scan times vary significantly between protocols depending on number and type of sequences used.…”
Section: Technical Factors: Sequences and Imaging Planesmentioning
confidence: 99%
See 4 more Smart Citations
“…Considerable site-to-site variations arise from differing scanner platforms and technological capabilities, the tumors and syndromes under surveillance, and departmental/radiologist preference. The most recent published protocols specific for WBMRI in pediatric oncology utilize a fluid-sensitive sequence in the coronal plane, with additional optional sequences and imaging planes (1,(6)(7)(8)(17)(18)(19), and are summarized in Table 2. As documented in the table, scan times vary significantly between protocols depending on number and type of sequences used.…”
Section: Technical Factors: Sequences and Imaging Planesmentioning
confidence: 99%
“…One pediatric study by Nievelstein and Littooij compared WBMRI with PET/CT and found MRI was better able to identify bony infiltrates <12 mm (8). Although lung nodules are increasingly identified on WBMRIsome studies showing high sensitivities for lesions between 4 and 10 mm-WBMRI screening for pulmonary metastases is not yet advocated, and chest CT remains the reference standard (5,6 As well as a systematic approach and detailed knowledge improving lesion detection, as Anupindi and colleagues highlighted, it is equally important to carry out "risk stratification" to minimize false positive findings (18). WBMRI is only one part of a surveillance program, and findings should be interpreted in conjunction with other clinical and imaging data (17,18).…”
Section: Wbmri Interpretation and Reportingmentioning
confidence: 99%
See 3 more Smart Citations